Quality Management Analysis in Non-formal Arabic Language Educational Institutions Based on National Education Standards - Ardianysah, Muhammad; Ihsan, Muhammad; Satyaningrum, Retnowati (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Quality management evaluation is essential for both formal and non-formal educational institutions, particularly in the context of Arabic language learning at the Al Azhar Arabic Language Course in Pare, Kediri. This study adopts a qualitative method with a case study approach to investigate the quality management practices in place. Primary data were collected through interviews with educators and students, while secondary data were obtained from relevant literature. The data collection techniques included structured interviews, and the analysis was conducted using Miles and Huberman's framework, which consists of data collection, data reduction, data presentation, and conclusion drawing and verification. The findings indicate that the learning process at Al Azhar Pare is highly enjoyable, fostering student engagement. However, the evaluation of the quality management of Arabic language learning identifies two critical areas for improvement based on the eight educational quality management standards: the need for comprehensive attitude and spiritual assessments, and enhanced training programs to improve educator competencies. The novelty of this evaluation lies in the emphasis on the importance of a structured training system and comprehensive assessments of students' attitudes and skills